KOMODIFIKASI ASKETISME ISLAM JAWA: EKSPANSI PASAR PARIWISATA DAN PROSTITUSI DI BALIK TRADISI ZIARAH DI GUNUNG KEMUKUS (Harmoni, 2013)
The tradition of pilgrimage at the tomb of the Prince Samudra, Mount Kemukus, Sragen in Central Java is one form of Islamic Java asceticism interesting to talk about, because it is always associated with seeking pesugihan ritual (ritual to seek wealth unseen) through deviant sex. Departing from the reality of commodification of ritual Islamic asceticism on Mount Kemukus, the following study examine the effects of market expansion in tourism and prostitution behind tradition of pilgrimage on Mount Kemukus. In the history from the eighties, the expansion of the tourism market and prostitution cause ngalap berkah ritual (ritual to get blessing) which was part of the expression, likely to cause a deviation the myth ΓÇ£sex ritualsΓÇ¥ behind the pilgrimage activities. As a result, the practice of Islamic Java asceticism is experiencing commoditization, as well as uprooted from cultural roots and Islamic Java Faith. The study shows that the existence of Islamic Java asceticism on Mount Kemukus characterized by the practice of ritual sex can be portrayed as a symptom of the doctrine of asceticism deviation, both in the Hindu, Buddhist, and Islamic. The practice is increasingly strong deviation, because the effect of the expansion of the tourism market, especially when it makes ΓÇ£sexΓÇ¥ as a commodity for capital accumulation. Images of sex ritual tradition of pilgrimage to the tomb of Prince Samudra, Mount Kemukus it has strengthened its assumptions about the nature of Islamic Java asceticism is ambiguous. On the one hand, the pilgrims perform the practice of asceticism to unite with Good, seek the path of God, but on the other hand the practice of Islamic Java asceticism also aims to achieve pleasure and worldly desires such as wealth, prestige, and other worldly success.
Keywords: Prostitusi dan Ziarah; Pasar Pariwisata; Ekspansi; Islam Jawa; Asketisme; Komodifikasi